Chemical and Biochemical Properties of Verjuice Obtained from Vitis labrusca Grapes by Using Different Extraction Methods - Soares LDS; Sant’Anna V; Leães FL; Weber FH; Furlan JM; Clerici NJ; Brandelli A; Crepalde LT; Dupas de Matos A (MDPI (Basel, Switzerland), 2025)
Verjuice, a green grape juice traditionally produced from grapes obtained through thinning, represents a sustainable alternative for the utilization of viticulture by-products. No standardized methods of production are utilized to make verjuice, highlighting the need for further research. This study evaluated three extraction methods—pressing extraction (PE), steam extraction (SE), and centrifuge juicer extraction (CJE)—to produce verjuice from three Vitis labrusca varietals (Bordô, Concord, and White Niágara). Physicochemical parameters, volatile compounds (VOC), total polyphenol content, antioxidant and anti-hypertensive activities were analyzed. Extraction method and grape varietal influenced physicochemical composition, antioxidant capacity, and VOC. The SE method resulted in higher yields but lower polyphenolic content, while the CJE was more efficient in extracting phenolic compounds and preserving antioxidant properties. Higher concentrations of malic acid were observed in verjuice extracted by PE and CJE methods from Bordô and Concord grapes, while higher tartaric acid content was found in Bordô and Niágara grapes extracted by CJE. Within grapes, verjuices presented wider volatile profile than those described in the literature, and CJE and PE methods yielded higher amounts of VOC. Thus, V. labrusca presents great potential to produce verjuices and CJE shows to be an efficient alternative to the pressing method.
Keywords: unripe grape juice; steam extraction; centrifuge extraction; pressing extraction; volatile compounds; antioxidant activity